Effects of Spin-orbit Interaction on Persistent Current in a Nano Ring. (2015) - Monisha P.J.,; Sankar, I.V.; Sil, Shreekantha; Chatterjee, Ashok
Abstract: The persistent current for polaronic transport in a one dimensional Holstein-Hubbard ring is studied in the presence of Rashba spin orbit (RSO) interaction. The energy is calculated within the Hartree-Fock approximation, using Lang-Firsov transformation followed by block diagonalization. We have found that the strong electron-phonon interaction will reduce the persistent current while the spin-orbit interaction enhances the amplitude of the persistent current. The Drude weight is also calculated.